Pengembangan Media Pembelajaran Intelligent Math Snake (IMS) untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa - Apriyanti, Sindy; Zaenal, Reza Muhamad; Yusritawati, Ita (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to design a snakes and ladders game media and determine the feasibility and effectiveness of Intelligent Math Snake (IMS) learning media to improve students' mathematical understanding skills, especially on flat-sided space building material. This research uses development research or Research and Development (R&D) with the ADDIE development model. The sample in this study were students of class VIII-H MTs Negeri 7 Kuningan in the 2023/2024 school year. The data analysis technique used in this study used the Paired Sample T Test, N-Gain test, and questionnaire processing. From the results of the study, it was found that the Intelligent Math Snake (IMS) learning media developed was feasible to use in learning based on the verification results of media experts and material experts. The Intelligent Math Snake (IMS) learning media developed effectively improves students' mathematical understanding skills. This can be seen from the average student mathematical understanding test scores after using Intelligent Math Snake (IMS) learning media higher than before. The development of Intelligent Math Snake (IMS) learning media received good responses from students.  This can be seen from the survey results of student response questionnaires to the Intelligent Math Snake (IMS) learning media